Input ekologi dalam penilaian impak alam sekitar (EIA) bagi langkah penebatan untuk aktiviti kuari di Malaysia - Rahimah Wahid,; A. Latiff Mohamed,; Mohd. Pauzi Abdullah, (Environmental Management Society, Malaysia, 2010)
The assessment of ecological inputs is important in the process of the development especially that linked with the mitigation measures. The review method for quarry activities was carried out using Ecological Input Assessment for Quarry Activity Package. Results obtained were recorded and analysed to get the percentage and the total number of reports from the aspect of the adequacy of ecological information and the compliance towards the existing provision and regulation. The marking score (1-6) was used to measure the adequacy of some parameters. There were many weaknesses in the reviewed EIA reports with respect to mitigation measures. Most of the mitigation measures proposed was only temporary in nature and quite limited in controlling the destruction of the ecology of the quarry sites. There was some mitigation measures proposed that was not carried out and complied by the project proponents. The reports also did not state whether the mitigation measures were effective and implement able. Suggestions to improve the mitigation measures in the EIA reports were made with certain conditions, including those that further improve the existing guidelines